ChemInform Abstract: Copper‐Catalyzed Regio‐ and Stereoselective Hydroallylation of Thioalkynes with Allylboronates: A Facile and Convenient Synthesis of 1, 4‐Dienes. Issue 36 (September 2015) - Kong, Wei; Che, Chao; Kong, Lichun; Zhu, Gangguo
Abstract The hydroallylation reaction affords 1, 4‐dienyl sulfides in moderate to good yield.